Analysis of factors influencing electric vehicle purchase intention: TPB, NAT, and TCV perspectives - Yusrina Adzani; Ignatius Heruwasto (Sustinere: Journal of Environment and Sustainability, 2026)
The transportation sector is a major contributor to carbon emissions, yet the adoption of electric vehicles (EVs) in Indonesia remains limited. This study aims to examine the determinants of EV purchase intention by integrating the theory of planned behavior (TPB), Norm Activation Model (NAM), and Theory of Consumption Value (TCV), providing a more comprehensive understanding of both rational and moral drivers of consumer behavior. A quantitative approach was employed using an online survey, with 509 valid responses analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that conditional value, monetary value, perceived behavioral control, and personal norm significantly influence EV purchase intention, with conditional value emerging as the strongest predictor. These findings highlight the importance of situational benefits and cost considerations, alongside moral responsibility, in shaping consumer intentions toward EV adoption. This study contributes to the literature by offering an integrated framework that combines economic, behavioral, and normative perspectives, while also providing practical insights for policymakers and marketers to design more effective strategies to accelerate EV adoption in emerging markets.